Prospective methods for identifying perioperative risk‐assessment methods for patient safety over 20 years: a systematic review. Issue 2 (17th December 2019) - Heideveld‐Chevalking, A. J.; Calsbeek, H.; Hofland, J.; Meijerink, W. J. H. J.; Wolff, A. P.
Abstract : Background: Serious preventable surgical events still occur despite considerable efforts to improve patient safety. In addition to learning from retrospective analyses, prospective risk‐assessment methods may help to decrease preventable events further by targeting perioperative hazards. The aim of this systematic review was to assess the methods used to identify perioperative patient safety risks prospectively, and to describe the risk areas targeted, the quality characteristics and feasibility of methods. Methods: MEDLINE, Embase, CINAHL and Cochrane databases were searched, adhering to PRISMA guidelines. All studies describing the development and results of prospective methods to identify perioperative patient safety risks were included and assessed on methodological quality. Exclusion criteria were interventional studies, studies targeting one specific issue, studies reporting on structural factors relating to fundamental hospital items, and non‐original or case studies. Results: The electronic search resulted in 16 708 publications, but only 20 were included for final analysis, describing five prospective risk‐assessment methods. Direct observation was used in most studies, often in combination. Direct (16 studies) and indirect (4 studies) observations identified (potential) adverse events (P)AEs, process flow disruptions, poor protocol compliance and poor practice performance. (Modified) Healthcare Failure Mode and Effect Analysis (HFMEA™) (5 studies) targeted potential process flow disruption failures, and direct (P)AE surveillance (3 studies) identified (P)AEs prospectively. Questionnaires (3 studies) identified poor protocol compliance, surgical flow disturbances and patients' willingness to ask questions about their care. Overall, quality characteristics and feasibility of the methods were poorly reported. Conclusion: The direct (in‐person) observation appears to be the primary prospective risk‐assessment method that currently may best help to target perioperative hazards. This is a reliable method and covers a broad spectrum of perioperative risk areas. Abstract : Serious preventable surgical events continue to occur despite considerable efforts to improve patient safety. This systematic literature review provides an overview of prospective risk‐assessment methods used proactively to identify and target hazardous failures and preventable patient harm in perioperative patient care. Patient safety risk factors Abstract : Antecedentes: A pesar de los esfuerzos considerables para mejorar la seguridad del paciente, aún se producen complicaciones quirúrgicas graves prevenibles. Además de adquirir conocimientos a través de los análisis retrospectivos, los métodos de evaluación de riesgos prospectivos por su enfoque en los riesgos perioperatorios, pueden ayudar a disminuir aún más los efectos adversos prevenibles. Esta revisión sistemática tiene como objetivo evaluar los métodos utilizados para identificar de forma prospectiva los riesgos perioperatorios de seguridad del paciente, describiendo las áreas de riesgo y las características de calidad y viabilidad de los métodos. Métodos: Se realizaron búsquedas en las bases de datos MEDLINE, EMBASE, CINAHL y Cochrane siguiendo las recomendaciones PRISMA. Se incluyeron todos los estudios que describían el desarrollo y los resultados de métodos prospectivos para identificar los riesgos perioperatorios de seguridad del paciente y se evaluó su calidad metodológica. Se excluyeron los estudios de intervención, aquellos estudios dirigidos a un tema específico, los estudios enfocados a factores estructurales relacionados con elementos hospitalarios clave, y los estudios no originales o series de casos. Resultados: La búsqueda electrónica identificó 16.708 publicaciones, pero solamente se incluyeron 20 publicaciones en las que se describían 5 métodos prospectivos de evaluación de riesgos. La observación directa fue el método utilizado en la mayoría de los estudios, a menudo en combinación con métodos indirectos. Las observaciones directas (80%) e indirectas (20%) identificaron efectos adversos potenciales ( potential adverse events, (P)AEs), disrupciones en el flujo de los procesos, baja adherencia a los protocolos y prácticas deficientes. El análisis (modificado) de fallo de la atención sanitaria por modo y efecto ( Healthcare‐Failure‐Mode‐and‐Effect Analysis ) (25%) enfocado a fallos potenciales de disrupción de los procesos y la vigilancia directa de los (P)AEs (16%) identificaron (P)AEs de forma prospectiva. Los cuestionarios (15%) identificaron una baja adherencia a los protocolos, alteraciones en el flujo del proceso quirúrgico y la disposición de los pacientes para hacer preguntas sobre su atención. En general, las características de calidad y la viabilidad de los métodos se describían de manera deficiente. Conclusión: La observación directa (en persona) es el principal método prospectivo de evaluación de riesgos que actualmente podría ser el mejor método para el enfoque en los riesgos perioperatorios. Es un método confiable y cubre un amplio espectro de áreas de riesgo perioperatorio.